Nanoscale squeezing in elastomeric nanochannels for single chromatin linearization - Matsuoka, Toshiki (2012)
This paper describes a novel nanofluidic phenomenon where untethered DNA and chromatin are linearized by rapidly narrowing an elastomeric nanochannel filled with solutions of the biopolymers. This nanoscale squeezing procedure generates hydrodynamic flows while also confining the biopolymers into smaller and smaller volumes. The unique features of this technique enable full linearization then trapping of biopolymers such as DNA. The versatility of the method is also demonstrated by analysis of chromatin stretchability and mapping of histone states using single strands of chromatin.